Pulmonary paragonimiasis presenting as massive empyema requiring decortication in an adolescent: a case report - Kyo Jin Jo; Su Eun Park; Jong Myung Park; Joo-Young Na; Sungsu Jung (Journal of Medical Case Reports)
Abstract Introduction Pulmonary paragonimiasis is a parasitic infection caused by lung flukes of the Paragonimus genus, primarily acquired by consuming raw or undercooked freshwater crustaceans. Despite improvements in sanitation, paragonimiasis, once widespread in Asia, remains a concern due to its potential for re-emergence in endemic regions such as Korea. The infection typically begins when metacercariae are ingested, excyst in the intestine, and migrate to the lungs, causing pleuritis and pneumonia. However, large empyema cases associated with paragonimiasis, especially in pediatric patients, are exceedingly rare. Case presentation A 14-year-old Korean adolescent presented to the emergency clinic with dyspnea, cough, and blood-tinged sputum. Her symptoms had worsened over 5 months, and she had recently developed a fever. Physical examination revealed decreased breath sounds in the left lung, and chest computed tomography revealed a small cavitary nodule and a collapsed left lung with massive pleural effusion displacing the mediastinum. The pleural fluid was turbid and yellowish, indicative of empyema. Laboratory tests indicated eosinophilia with an absolute eosinophil count of 970 cells/μL, and further investigation confirmed pulmonary paragonimiasis through the detection of Paragonimus eggs in bronchoalveolar lavage fluid. Oral praziquantel was administered, but residual atelectasis necessitated video-assisted thoracic surgery for decortication. Histopathology confirmed Paragonimus eggs in pleural tissue, and lung function improved postsurgery. Conclusion Due to recent improvements in sanitation, cases of pulmonary paragonimiasis in the pediatric population progressing to surgical decortication are extremely rare. This case highlights the importance of considering parasitic infections in children with cavitary lung lesions, particularly in endemic regions. Despite significant reductions in the prevalence of paragonimiasis, clinicians must remain vigilant, especially in patients with a history of consuming freshwater crustaceans. Effective treatment with praziquantel and, in severe cases, surgical decortication can lead to successful outcomes.